2022
DOI: 10.53808/kus.2018.15.1and2.1706-s
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Career Choice of the Female Secondary Students in Khulna District of Bangladesh

Abstract: Career choice is a growing issue all over the world as secondary students usually face with a dilemma in making an appropriate career choice decision in their lives. For this reason, the study aimed to explore the factors that influence the career choices among female secondary students in Bangladesh. Following survey research design a semi-structured questionnaire was administered to collect data from 181 randomly selected female students of class six to ten from two secondary schools of Chalna Pourashava und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Prior national and international studies consistently found that students with high self-efficacy outperform students with low self-efficacy (Huang, 2013;Shaine, 2015;Tizazu and Ambaye, 2017). Moreover, studies depict that self-efficacy determines students' career decision-making (Ogutu et al, 2017;Akter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior national and international studies consistently found that students with high self-efficacy outperform students with low self-efficacy (Huang, 2013;Shaine, 2015;Tizazu and Ambaye, 2017). Moreover, studies depict that self-efficacy determines students' career decision-making (Ogutu et al, 2017;Akter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Prior national and international studies consistently found that students with high self-efficacy outperform students with low self-efficacy (Huang, 2013;Shaine, 2015;Tizazu and Ambaye, 2017). Moreover, studies depict that self-efficacy determines students' career decision-making (Ogutu et al, 2017;Akter et al, 2018).…”
Section: Introductionmentioning
confidence: 99%